Potensi dan Pengembangan Pariwisata di Kabupaten Pemalang Tahun 2010 DAN 2014 - Setiawan, Wahyu Adhi, Dr. H. Kuswaji Dwi Priyono, M.Si, Dra. H. Umrotun, M.Si (2016)
This study entitled "The Potential and Development of Tourism in Pemalang in 2010 and 2014". The first formulation of the problem, how the various attractions that have the highest potential in Pemalang Regency ?, then the both, how the development of priority tourism in Pemalang ?. This study aims to: 1) determine variations tourist attraction with the most potential in Pemalang, 2) determine the priority development of tourism in Pemalang. The method used in this study with the primary and secondary data analysis, while the method used for the analysis region is SWOT (Strength, Weakness, Oportunity, Threat) analysis in order to formulate a strategy towards the development of tourism. Primary data were obtained in the field of data in the form of interviews with tourism managers. Secondary data were obtained from the collection of data from the agencies concerned. SWOT analysis is done to determine the potential of internal and external tourism in the study area. The results showed that the Blendung Beach is in first position in its development because it has a score of 34 combined potential. The potential internal score is 13 and the external score is 21. Widuri Water Park is located at the second position even if the combined potential score is 34 but on the potential of the internal score is 12 and the potential of the external score is 22. The third position in the development process is the Ventura River, where the object is to have the combined potential score is 33, internal potential score is 11, and the external potential scoren is 22. Last, Lake Silating have a combined potential score is 30, the potential of the internal score is 10 and the external potential is 20.